Safety and efficacy of ticagrelor and clopidogrel in primary percutaneous coronary intervention - Velders, Matthijs A.; Abtan, Jérémie; Angiolillo, Dominick J.; Ardissino, Diego; Harrington, Robert A.; Hellkamp, Anne; Himmelmann, Anders; Husted, Steen; Katus, Hugo; Meier, Bernhard; Schulte, Phillip J.; Storey, Robert F.; et al. (Heart, 2016)
Objective The effects of ticagrelor in the subpopulation of patients with ST-elevation myocardial infarction (STEMI) were consistent with those observed in the overall Platelet Inhibition and Patient Outcomes (PLATO) study. However, this subgroup included patients initially or ultimately treated conservatively. The aim of this study is to compare treatment using ticagrelor with treatment using clopidogrel in patients with STEMI undergoing primary percutaneous coronary intervention (PCI). - Methods This post-hoc subgroup analysis compared ticagrelor with clopidogrel in 4949 PLATO patients with STEMI that were treated with primary PCI within 12 h of admission. The primary endpoint was cardiovascular death, myocardial infarction or stroke. The safety endpoint consisted of any major bleeding. Secondary endpoints included stent thrombosis. The analysis was not adequately powered to establish significance of any treatment effects. - Results During a median of 286 days, the primary endpoint occurred in 7.9% of ticagrelor-treated patients versus 8.6% of clopidogrel-treated patients (HR 0.91, 95% CI 0.75 to 1.12, p=0.38). Major bleeding occurred in 6.7% in ticagrelor-treated patients versus 6.8% of clopidogrel-treated patients (HR 0.97, 95% CI 0.77 to 1.22, p=0.79). No interactions were observed for the treatment effect of ticagrelor versus clopidogrel on the primary efficacy (p=0.40) and primary safety endpoints (p=0.15) as compared with the full PLATO population. Treatment with ticagrelor versus clopidogrel reduced the occurrence of definite stent thrombosis (HR 0.58, 95% CI 0.37 to 0.89, p=0.013). - Conclusions In the subset of patients with STEMI treated with primary PCI, ticagrelor compared with clopidogrel was safe, and efficacy outcomes were consistent with the overall PLATO trial. - Trial registration number NCT00391872; Results.